3 x square - 2 X + one upon 3 is equals to zero solve the quadratic equation
Answers
Answered by
1
(3x²-2x+1)/3=0,
then
3x²-2x+1=0,
x=[2+-√(4-4×3×1)]/(2×3),
x=[2+-√(4-12)]/6,
x=[2+-√(-8)]/6,
x=[2+-(2√2i)]/6
then
3x²-2x+1=0,
x=[2+-√(4-4×3×1)]/(2×3),
x=[2+-√(4-12)]/6,
x=[2+-√(-8)]/6,
x=[2+-(2√2i)]/6
marie10:
i have updated another quest plz ans it
Answered by
2
3x^2 - 2x + 1/3 =0
[multiply with 3 on both sides...
9x^2 - 6x + 1=0
9x^2 -3x -3x +1=0
3x(3x-1) -1(3x-1)=0
(3x-1)^2=0
3x-1=0
x=1/3
Similar questions